Pelaksanaan Tugas dan Wewenang Pemerintah Desa dalam Mengelola Desa Wisata di Kecamatan Boleng, Kabupaten Manggarai Barat (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to analyze the implementation of the duties and authorities of the village government in managing tourist villages in Boleng District, West Manggarai Regency. This research is empirical juridical research, which is research directly to related parties to obtain primary data directly from respondents. The data collection technique uses interviews, observations, and literature/document studies. The data used are primary data and secondary data. This research was conducted in West Manggarai Regency. The results of the data processing were analyzed descriptively using the empirical juridical method, namely identifying and adjusting to the actual situation. The results showed that: the implementation of the duties and authority of the Village Government in carrying out its duties and responsibilities is in accordance with existing procedures, but in providing duties and responsibilities for the management of the Tourism Village has not been evenly distributed and has not been given the trust to manage the Tourism Village by the Regional Government. Based on the experience in the field and the information obtained, the researcher can provide suggestions and input to the Golo Lujang Village Government so that it can maximize its role, especially in managing the